2023
DOI: 10.2196/44649
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Public Health Digital Surveillance Systems for Infectious Disease Prevention and Control at Mass Gatherings: Systematic Review

Abstract: Background Mass gatherings (MGs; eg, religious, sporting, musical, sociocultural, and other occasions that draw large crowds) pose public health challenges and concerns related to global health. A leading global concern regarding MGs is the possible importation and exportation of infectious diseases as they spread from the attendees to the general population, resulting in epidemic outbreaks. Governments and health authorities use technological interventions to support public health surveillance and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(167 reference statements)
0
0
0
Order By: Relevance
“…This would further strengthen standardization in capacity assessment and resource allocation initiatives in Africa. Previous studies ( 25 ) have revealed that digitalization improves timeliness in reporting. It would be important for stakeholders to consider including digitalization as a critical parameter when evaluating surveillance systems.…”
Section: Recommendationsmentioning
confidence: 97%
See 1 more Smart Citation
“…This would further strengthen standardization in capacity assessment and resource allocation initiatives in Africa. Previous studies ( 25 ) have revealed that digitalization improves timeliness in reporting. It would be important for stakeholders to consider including digitalization as a critical parameter when evaluating surveillance systems.…”
Section: Recommendationsmentioning
confidence: 97%
“…Previous studies ( 25 ) have revealed that digitalization improves timeliness in reporting. It would be important for stakeholders to consider including digitalization as a critical parameter when evaluating surveillance systems.…”
Section: Recommendationsmentioning
confidence: 97%
“…The data sources, which include notifications and case reporting from laboratories, general practitioners, and hospitals, are the most common sources of information for case-based communicable disease reporting systems and other sources (healthcare-based or not) can also be included in a public health reporting system (12). Furthermore, epidemiological investigations were carried out with close contact tracing by Public Health Center Tracers.…”
Section: Surveillance Proceduresmentioning
confidence: 99%